Dynamic Pain Phenotypes are Associated with Spinal Cord Stimulation‐Induced Reduction in Pain: A Repeated Measures Observational Pilot Study. Issue 7 (20th March 2015) - Campbell, Claudia M.; Buenaver, Luis F.; Raja, Srinivasa N.; Kiley, Kasey B.; Swedberg, Lauren J.; Wacnik, Paul W.; Cohen, Steven P.; Erdek, Michael A.; Williams, Kayode A.; Christo, Paul J.
Abstract: Objective: Spinal cord stimulation (SCS) has become a widely used treatment option for a variety of pain conditions. Substantial variability exists in the degree of benefit obtained from SCS and patient selection is a topic of expanding interest and importance. However, few studies have examined the potential benefits of dynamic quantitative sensory testing (QST) to develop objective measures of SCS outcomes or as a predictive tool to help patient selection. Psychological characteristics have been shown to play an important role in shaping individual differences in the pain experience and may aid in predicting responses to SCS. Static laboratory pain‐induction measures have also been examined in their capacity for predicting SCS outcomes. Methods: The current study evaluated clinical, psychological and laboratory pain measures at baseline, during trial SCS lead placement, as well as 1 month and 3 months following permanent SCS implantation in chronic pain patients who received SCS treatment. Several QST measures were conducted, with specific focus on examination of dynamic models (central sensitization and conditioned pain modulation [CPM]) and their association with pain outcomes 3 months post SCS implantation. Results: Results suggest few changes in QST over time. However, central sensitization and CPM at baseline were significantly associated with clinical pain at 3 months following SCS implantation, controlling for psycho/behavioral factors and pain at baseline. Specifically, enhanced central sensitization and reduced CPM were associated with less self‐reported pain 3 months following SCS implantation. Conclusions: These findings suggest a potentially important role for dynamic pain assessment in individuals undergoing SCS, and hint at potential mechanisms through which SCS may impart its benefit.